Determinants of community pharmacy utilisation among the adult population in Malaysia: findings from the National Health and Morbidity Survey 2019 - Normaizira Hamidi; Yeung R'ong Tan; Suhana Jawahir; Ee Hong Tan (BMC, 2021)
Abstract Background Community pharmacies provide alternatives for medication procurement and other basic and minor health-related services in addition to mainstream hospitals and primary healthcare services. This study aimed to determine the characteristics of community pharmacy users and associated factors for community pharmacy utilisation in Malaysia. Methods Secondary data analysis was performed using data from the National Health and Morbidity Survey 2019, a nationwide cross-sectional household survey that used a two-stage stratified random sampling design. Adults aged 18 years and over were included in the analysis. Respondents who reported visiting the community pharmacy for health purposes two weeks prior to the study were considered as users. Complex sample descriptive statistics were used to describe the respondents' characteristics. Logistic regression analyses were employed to determine factors associated with community pharmacy utilisation. Results Of the 11,155 respondents interviewed, 10.3 % reported community pharmacy utilisation for health purposes. Females (OR = 1.41, 95 % CI = 1.14, 1.73), those with tertiary education (OR = 2.03, 95 % CI = 1.26, 3.29), urban dwellers (OR = 1.42, 95 % CI = 1.13, 1.79), and those with self-reported health problems (OR = 7.62, 95 % CI = 6.05, 9.59) were more likely to utilise the community pharmacy. Conclusions Demographic and socioeconomic factors were important determinants of community pharmacy utilisation in Malaysia with sex, age, education level, locality, and self-reported health problems as the associated factors. These findings serve as evidence for policy interventions, crucial for improvements in accessibility to healthcare services.